Spontaneous Loculated Bilateral Hydropneumothoraces in a Patient with Recent COVID-19 Infection - Jacques Lowe; Bradley Kaptur; Ali Baltaji; Daniel Rosenblat; James Kumar; Vishesh Paul (Case Reports in Medicine)
A 53-year-old male presented to the emergency room with chest pain, shortness of breath, and back pain. He had recently recovered from COVID-19 infection and returned home on room air. Chest imaging showed bilateral hydropneumothoraces that were not present on the imaging performed during his prior admission three weeks ago. The patient was treated with bilateral chest tube drainage and oxygen support and responded well to treatment. This case represents a unique occurrence of spontaneous loculated bilateral hydropneumothoraces in the context of recent clinical recovery from COVID-19 infection requiring inpatient treatment. This case highlights the importance of an awareness of a potential sequela of COVID-19 that may occur even after presumed clinical recovery.